Immature stages of Murgantia histrionica (Hemiptera: Pentatomidae) - Brito, Lucas Cavalcanti; Santos, Suelle Maria Dos; Barão, Kim Ribeiro (Zootaxa, 2018)
Immature stages of Murgantia histrionica (Hemiptera: Pentatomidae) are described using light and scanning electron microscopy. Specimens of all life stages of M. histrionica were collected on Peritoma arborea (Cleomaceae) in Palm Springs, California. Specimens were observed in light and scanning microscopies, imagens taken and described based on specimens and photographs. We provide images of the eggs and immatures in light microscopy, and SEM of the eggs and first and fifth instars. Eggs of M. histrionica are barrel-shaped, white, with brown band and circular spot; the corium surface carinated, forming hexagonal cells; carinae irregular apically. The nymphal color pattern; the reflexed lateral margins of pro- and mesothorax; and the scattered punctuation of the tegument are a combination of characteristics enabling M. histrionica identification in its nymphal stages. The eggs of M. histrionica are similar in shape, color, and size to other Strachiini genera, such as Bagrada, Eurydema and Stenozygum. Among the Strachiini, the correct identification of M. histrionica based on immatures is possible by the shape of the head and pronotum, overall size of immatures, and coloration patterns.